1999
DOI: 10.1128/jb.181.20.6463-6468.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Single-Stranded DNA-Binding Protein of Bacteriophage P1

Abstract: The genome of bacteriophage P1 harbors a gene coding for a 162-amino-acid protein which shows 66% amino acid sequence identity to the Escherichia coli single-stranded DNA-binding protein (SSB). The expression of the P1 gene is tightly regulated by P1 immunity proteins. It is completely repressed during lysogenic growth and only weakly expressed during lytic growth, as assayed by anssb-P1/lacZ fusion construct. When cloned on an intermediate-copy-number plasmid, the P1 gene is able to suppress the temperature-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In addition, D6 encodes homologues of the P1 “defense against restriction” proteins Ulx, DarA, DarB, DdrA and Hdf (33 to 64% identical to their D6 homologues; table S1) (Piya et al , 2017 and references therein), and the P1 Hot and HumD homologues of the theta subunit of bacterial DNA polymerase III (Chikova and Schaaper, 2007) and of the UmuD’ subunit of E. coli DNA polymerase V (McLenigan et al , 1999), respectively. D6 orf115 is predicted to encode a dUTPase (deoxyuridine 5′-triphosphate nucleotidohydrolase) that has no P1 homologue, and the P1 ssb gene that encodes a single-strand DNA binding protein (Lehnherr et al , 1999) has no D6 homologue.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, D6 encodes homologues of the P1 “defense against restriction” proteins Ulx, DarA, DarB, DdrA and Hdf (33 to 64% identical to their D6 homologues; table S1) (Piya et al , 2017 and references therein), and the P1 Hot and HumD homologues of the theta subunit of bacterial DNA polymerase III (Chikova and Schaaper, 2007) and of the UmuD’ subunit of E. coli DNA polymerase V (McLenigan et al , 1999), respectively. D6 orf115 is predicted to encode a dUTPase (deoxyuridine 5′-triphosphate nucleotidohydrolase) that has no P1 homologue, and the P1 ssb gene that encodes a single-strand DNA binding protein (Lehnherr et al , 1999) has no D6 homologue.…”
Section: Resultsmentioning
confidence: 99%
“…The ssb‐1 mutation is an alteration of amino acid 55 from a histidine to a tyrosine, which is believed to destabilize the tetrameric SSB protein complex upon shifting temperature from 30°C to the non‐permissive temperature of 43°C, resulting in a lethal phenotype (Chase et al , 1983). Overexpression of wild‐type E. coli SSB protein encoded on a plasmid can overcome the lethality of the mutation (Chase et al , 1983) as can the SSB protein of bacteriophage P1 (Lehnherr et al , 1999). To test the in vivo functionality of SsoSSB, the protein was overexpressed in the E. coli strain KLC789 that carries the ssb‐1 allele.…”
Section: Resultsmentioning
confidence: 99%
“…SSB-P1 can substitute for E. coli SSB. Previous experiments showed that SSB-P1 was able to restore growth to a temperature-sensitive mutant of E. coli (29) at the nonpermissive temperature of 42°C (18,24). The defect in the E. coli SSB, leading to the temperature-sensitive phenotype, interferes with the essential ability of SSB to form stable tetramers (29).…”
Section: Phylogenetic Analysis Of Ssb-p1mentioning
confidence: 99%
“…Growth phase-dependent expression of ssb-P1. The construction of plasmid pHAL252, carrying an ssb-P1::lacZ indicator fusion was described previously (24). The rpoS strain RH90 and the isogenic wild-type strain MC4100 were transformed with pHAL252.…”
mentioning
confidence: 99%
See 1 more Smart Citation